2020
DOI: 10.1016/j.nicl.2020.102410
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function abnormalities in cortical sensory projections in embouchure dystonia

Abstract: Highlights Abnormal diffusion metrics are observed in sensory(motor) projections in ED. Left S1-putamen trajectory diffusion changes associate with putaminal FC reduction. Sensory cortex-related changes support a key role of sensory dysfunction in ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…For dMRI studies, using more diffusion directions can improve the precision of the calculated diffusion tensor, and a greater degree of diffusion weighting (a higher b value) can enable assessment of more subtle diffusion properties but with the trade‐off of increased potential for artifacts and lower signal to noise ratio. Of the studies identified, the number of diffusion directions ranged from 6 ( n = 5) [9–13] to ≥60 ( n = 18) [14, 31, 33, 35, 37, 39, 42–45, 49–51, 54, 57–59, 63], the remaining studies using an intermediate number of directions ( n = 10) [30, 32, 34, 36, 38, 40, 41, 46, 52, 53, 55, 56, 60–62, 64–68, 70] or no details were provided ( n = 1) [15]. The b values employed were in typical ranges of 700–1000 s/mm 2 , with five higher at 1100–1500 s/mm 2 [38, 39, 49–51].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For dMRI studies, using more diffusion directions can improve the precision of the calculated diffusion tensor, and a greater degree of diffusion weighting (a higher b value) can enable assessment of more subtle diffusion properties but with the trade‐off of increased potential for artifacts and lower signal to noise ratio. Of the studies identified, the number of diffusion directions ranged from 6 ( n = 5) [9–13] to ≥60 ( n = 18) [14, 31, 33, 35, 37, 39, 42–45, 49–51, 54, 57–59, 63], the remaining studies using an intermediate number of directions ( n = 10) [30, 32, 34, 36, 38, 40, 41, 46, 52, 53, 55, 56, 60–62, 64–68, 70] or no details were provided ( n = 1) [15]. The b values employed were in typical ranges of 700–1000 s/mm 2 , with five higher at 1100–1500 s/mm 2 [38, 39, 49–51].…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies identified, the number of diffusion directions ranged from 6 ( n = 5) [9–13] to ≥60 ( n = 18) [14, 31, 33, 35, 37, 39, 42–45, 49–51, 54, 57–59, 63], the remaining studies using an intermediate number of directions ( n = 10) [30, 32, 34, 36, 38, 40, 41, 46, 52, 53, 55, 56, 60–62, 64–68, 70] or no details were provided ( n = 1) [15]. The b values employed were in typical ranges of 700–1000 s/mm 2 , with five higher at 1100–1500 s/mm 2 [38, 39, 49–51].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations